The older they rise the younger they fall: age and performance trends in men's professional tennis from 1991 to 2012 - Kovalchik, S. A. (Journal of Quantitative Analysis in Sports, 2014)
In 2012, 3 out of 10 singles players in the top 100 on the Association of Tennis Professionals (ATP) World Tour were 30 years old or older - nearly a four-fold increase over 20 years ago, suggesting that the "old at 30" view in men`s tennis may be an old reality. In this paper, I investigate aging patterns among top ATP singles players between 1991 and 2012 and consider how surface effects, career length, and age at peak performance have influenced aging trends. Following a decade and a half of little change, the average age of top singles players has increased at a pace of 0.34 years per season since the mid-2000s, reaching an all-time high of 27.9 years in 2012. Underlying this age shift was a coincident rise in the proportion of 30-and-overs (29% in 2012) and the virtual elimination of teenagers from the top 100 (0% in 2012). Because the typical age players begin competing professionally has varied little from 18 years in the past two decades, career length has increased in step with player age. Demographics among top players on each of today`s major surfaces indicate that parallel aging trends have occurred on clay, grass, and hard court from the late 2000s forward. As a result of the changing age demographic over the past decade, the age of tennis`s highest-ranked singles players is now comparable to the age of elite long-distance runners. This evolution likely reflects changes in tennis play that have made endurance and fitness increasingly essential for winning success.